Proline, soluble sugar, leaf starch and relative water contents of four maize varieties in response to different watering regimes. (2016)
The purpose of this study was to evaluate the response of four maize varieties to different simulated watering regimes in term of proline, starch and soluble sugar contents as well as relative water content. Maize seeds were planted in 64 plastic pots of 20 litre capacity, arranged in a factorial fitted in completely randomized design (CRD), with four replications in the screen house of the Institute of Agricultural Research and Training (I.A.R&T), Moor Plantation Ibadan. The watering was done based on the designated field capacities (FC) of 25, 50, 75 and 100%. Fresh leaf samples were collected five weeks after planting and at the end of each stress period. The proline, soluble sugar, leaf starch and the relative water contents in the leaves were estimated. The results obtained showed that watering regime significantly influenced the leaf starch, soluble sugar, proline and relative water contents. The varieties also differ significantly in the proline, soluble sugar content, leaf starch and the relative water contents. Watering regime and variety interaction was significant for soluble sugar, starch, proline and the relative water content. Highest soluble sugar of 1.28 mg/g and proline of 35.70 μmol/g FW were obtained when FC was 25% and lowest when watering level was optimum. The starch and relative water contents were optimum under full watering (100% FC) and lowest when field capacity was 25%. Variations were observed with regards to different maize varieties. ART98SW6-OB accumulated the highest quantity of soluble sugar and proline under 25 and 50% field capacities alongside DTESYN, which is a drought tolerant maize variety. It could be concluded that water stress increased production of soluble sugar and proline, while water availability increases relative water content and favors starch accumulation. The consideration of these metabolites alongside other physiological features is a very fast and reliable method for drought tolerant plant selection even at the plant seedling growth stage.